Alex Cross must die : a thriller [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2023)
"An airport killer targeting pilots expands his scope. Alex Cross Must Die. "Drop whatever you're doing, Detective Cross, and head to Reagan Airport," DC Metro Police dispatch says. "A jet just crashed and exploded on the runway. The chief and the FBI want you and John Sampson there pronto." Cross and Sampson race to the crash site. The plane didn't fail--it was shot down by a stolen Vietnam War-era machine gun. The list of experts who can operate the weapon is short. And time before another lethal strike runs even shorter. Especially for Detective Cross. Alex Cross Must Die"--